Bacillus cereus strain isolated from Demodex folliculorum in patients with topical steroid-induced rosaceiform facial dermatitis - Alin Laurentiu Tatu; Marius Anton Ionescu; Victor Gabriel Clatici; Violeta Corina Cristea (Sociedade Brasileira de Dermatologia, 2016)
Abstract: The aim of the study was to identify Bacillus species from the Demodex folliculorum of patients with topical steroidinduced facial rosaceiform dermatitis. Of the 75 patients examined, 20% had clinical spinulosis, while 18.66% had dermoscopic features of Demodex: follicular plugs and tails. Of the 17.33% positive patients identified upon microscopy for Demodex, samples for bacterial culture were plated on trypticase soy Colombia agar. Identification was performed by microorganisms grown method mass spectrometry. We identified a strain of Bacillus cereus.